Oral health surveillance - Iba, Bemhemba; Dogoh, Aondover (Orapuh Journal, 2022)
Oral health surveillance is an ongoing process involving the collection, analysis, and interpretation of data to produce information for the prevention and control of oral diseases. The data obtained from surveillance are used basically for public health action – to prevent or control diseases. To review available literature on oral health surveillance, an electronic search for relevant literature was conducted. Database searches were carried out using the terms, oral health surveillance, surveillance, indicators of oral health, challenges of oral health surveillance, and sources of oral health indicators. This review is focused on discussing published information concerning the concept, objectives, indicators, sources, elements, and challenges of oral health surveillance. 39 papers published between 2003 and 2021 were selected, assessed, and included in this review. The review revealed that oral health surveillance is integral to the prevention of oral diseases and improving quality of life. Therefore, oral health policies should involve the integration of oral health surveillance into national and community health programmes, and oral health should be promoted as an effective, efficient, and essential part of policies aimed at promoting the overall wellbeing and general health of an individual.